(untitled) (Journal of the College of Basic Education, 2025)
The aim of the current research is to identify Career optimism, the significance of the difference in Career optimism according to the gender variable (males - females), and to identify self-efficacy. The significance of the difference in self-efficacy according to the gender variable (males - females). And to identify the correlation between Career optimism and self-efficacy among students of the Department of Psychological Counseling and Educational Guidance. The current research is limited to students of the Department of Psychological Counseling and Educational Guidance in the fourth stage at Al-Mustansiriya University and the University of Diyala of both genders (males - females) for the academic year (2024-2025) and for morning study. In order to achieve the research objectives, the researcher adopted Rottinghaus et al.’s (Rottinghaus et al., 2005) Career optimism scale, which consists of (11) items, prepared according to Savickas’s career building theory (Savickas, 2002). Sanjuan et al.’s (Sanjuan et al. 2000) self-efficacy scale, which consists of (10) items, was prepared according to Bandura’s social cognitive theory (Bandura, 1997), as the scales are suitable for the sample of the current research, after the researcher translated the scales and verified the validity of the translation and their psychometric properties. And stability. The sample was selected according to a simple random method and consisted of (150) male and female students. The results showed: that the research sample has a high degree of Career optimism, and there is no difference in Career optimism between males and females, and that the research sample has a high degree of self-efficacy, and there is no difference in self-efficacy between males and females, and that there is a statistically significant direct relationship. Between Career optimism and self-efficacy. In light of these results, the researcher recommended a number of recommendations and proposals.